Recurrence of hepatocellular carcinoma in patients with high HALP score in TACE combined with ablation - Fang, Da; Yin, Xue; Ding, Xiaoyan; Chen, Jinglong; Cui, Xiongwei; Hu, Caixia (Frontiers in Oncology, 2025)
ObjectivesTo investigate the relationship between the HALP score and recurrence in hepatocellular carcinoma (HCC) patients treated with transarterial chemoembolization (TACE) and ablation.MethodsWe collected clinical data from 728 HCC patients who underwent TACE and ablation from January 2018 to December 2023. Patients with high HALP scores (H-HALP, n=422) were stratified into a training cohort (n=296) and an internal validation cohort (n=126), while an external validation cohort (n=147) was independently enrolled. Lasso-Cox regression was employed to identify independent risk factors for recurrence-free survival (RFS), and a nomogram was constructed. The predictive accuracy of nomogram was evaluated using receiver operating characteristic (ROC) curves, calibration curves, and decision curve analysis (DCA).ResultsAlthough the median RFS in the H-HALP group longer than the L-HALP group (1.84 vs. 1.60 years, P=0.024), recurrence rates remained substantial in H-HALP patients (1-/3-/5-year RFS: 70.8%/36.2%/21.5%). The nomogram, integrating cirrhosis, tumor numbers, and γ-glutamyl transpeptidase (GGT), demonstrated moderate predictive accuracy for 1-/3-/5-year RFS in the training cohort (AUC: 0.665/0.694/0.671) and internal validation cohort (AUC: 0.622/0.606/0.561). External validation yielded AUCs of 0.569 (1-year), 0.615 (3-year), and 0.662 (4-year). Calibration curves indicated strong agreement between predicted and observed outcomes, while DCA confirmed clinical utility. Risk stratification based on nomogram scores revealed significantly prolonged RFS in low-risk versus high-risk groups across all cohorts.ConclusionThe HALP score alone showed limited prognostic value in this cohort; however, the Lasso-Cox regression-based nomogram effectively stratified recurrence risk in H-HALP patients treated with TACE and ablation.